2017
DOI: 10.1002/hec.3470
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Regional Variation of Cardiac Implantable Electrical Device Implant Rates in European Healthcare Systems: What Drives Differences?

Abstract: Despite established efficacy for cardiac implantable electrical devices (CIEDs), large differences in CIED implant rates have been documented across and within countries. The aim of this paper is to investigate the influence of socio-economic, epidemiological and supply side factors on CIED implant rates across 57 Regions in 5 EU countries and to assess the feasibility of using administrative data for this purpose. A total of 1 330 098 hospitalizations for CIED procedures extracted from hospital discharge data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Moreover, the programming may affect the occurrence of ICD therapy . The ICD implantation rate is lower in Sweden than in many comparable countries, which should be kept in mind when applying these findings to different contexts . While offering validated real‐world data, this is a smaller study, which increases the risk of type 2 errors.…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, the programming may affect the occurrence of ICD therapy . The ICD implantation rate is lower in Sweden than in many comparable countries, which should be kept in mind when applying these findings to different contexts . While offering validated real‐world data, this is a smaller study, which increases the risk of type 2 errors.…”
Section: Limitationsmentioning
confidence: 99%
“…However, using predefined algorithms to measure metastases and secondary tumours in administrative data alone has proven challenging elsewhere and should therefore be tested [38]. The reliability and completeness of coding for symptoms and treatment effects in administrative data can be sub-optimal, given marked variability in number and detail of diagnostic and procedure codes in administrative data, as has been found in multi-country projects [39][40][41]. Specific codes may be identified for some outcomes, but whether they are routinely recorded in hospital discharge summaries needs evaluation.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Therefore, in a subsequent phase of the research, reported in the third paper in this supplement, Torbica et al () undertook a new study of implant rates, the first to use the national hospital discharge datasets available in 5 EU countries. They provide evidence on differences in use of medical devices within and between member states, investigate the determinants of differences in access to CIEDs and assess the potential and limitations of administrative databases for the analysis of utilization rates of medical devices in electrophysiology.…”
Section: Geographical Variation In the Use Of Medical Devices In The Eumentioning
confidence: 99%